Venetoclax and hypomethylating agents in FLT3‐mutated acute myeloid leukemia. Issue 10 (28th July 2020) - Aldoss, Ibrahim; Zhang, Jianying; Mei, Matthew; Al Malki, Monzr M; Arslan, Shukaib; Ngo, Dat; Aribi, Ahmed; Ali, Haris; Sandhu, Karamjeet; Salhotra, Amandeep; Koller, Paul; Khaled, Samer; et al.
Abstract: FMS‐like tyrosine kinase 3 ( FLT3 ) mutations are prevalent in acute myeloid leukemia (AML), and their presence confers adverse risk. FLT3 ‐mutated ( FLT3m ) AML is a challenging leukemia to manage, particularly in older and unfit patients as well as patients with relapsed/refractory (r/r) disease. We retrospectively analyzed the outcomes of 50 FLT3m AML patients (17 treatment‐naïve, 33 r/r) treated with venetoclax (VEN) and hypomethylating agents (HMA). The overall CR/CRi rate with VEN‐HMA was 60% (94% in treatment‐naïve AML and 42% in r/r AML). Early (60‐days) treatment related mortality was 2%. The r/r AML setting was an independent predictor of lower complete response (OR: 0.08; 95%CI: 0.00‐0.60, P = .03). Cytogenetics‐molecular risk, concurrent mutations, the type of FLT3 mutation (ITD vs TKD), the ITD allelic ratio, the type of HMA, age, prior exposure to HMA and receipt of prior allogeneic transplant did not independently impact response or leukemia‐free survival (LFS). Concurrent IDH mutations were associated with lower CR/CRi ( P = .01), while ASXL1 or TET2 mutations showed a non‐significant association toward higher CR/CRi ( P = .07, for both). However, none of the concurrent mutations were an independent predictor for response when adjusted to AML setting. In conclusion, VEN‐HMA is associated with encouraging efficacy in FLT3m AML among both newly diagnosed unfit and r/r patients.